Examining parents' perceptions of their children's autism and completion of genetic testing. - Sakyi, Georgina J.; Mire, Sarah S.; Goin-Kochel, Robin P.; Murali, Chaya N.; Day, Susan X. (International Journal of Developmental Disabilities, 2025)
Though genetic testing is recommended for children diagnosed with autism spectrum disorder (ASD), both internal (e.g. parents' and providers' valuation of genetic testing) and external (e.g. insurance coverage) barriers exist, and exploration of these factors is required to close the gap between provider recommendations and parent follow-through. In a sample of 290 parents, we explored (a) how parents' ASD-related etiological beliefs and symptom attributions, as well as income, affected genetic testing completion; and (b) whether these factors influence parents' hopes or concerns about genetic testing. Principal component analysis (PCA) was used to investigate the factor structure of the ASD attribution measure used, which revealed a different factor structure from previous studies. Binomial logistic regression analyses indicated that parents were less likely to complete genetic testing when they believed their children's ASD was caused by their own personal attributes (e.g. their own stress, behaviors, attitudes, etc.). Parents' hopefulness about the utility of genetic testing increased when they observed more ASD symptoms. Results support the importance of understanding how parents' perceptions about ASD influence receptivity to and follow-through on genetic testing recommended by providers. Such information may enhance researchers' knowledge of parental decision-making regarding genetic testing and improve clinical care for ASD-affected families.